2018
DOI: 10.1136/bmjgh-2018-000757
|View full text |Cite
|
Sign up to set email alerts
|

Increasing participation in a vector control campaign: a cluster randomised controlled evaluation of behavioural economic interventions in Peru

Abstract: ObjectiveTo assess the efficacy of strategies informed by behavioural economics for increasing participation in a vector control campaign, compared with current practice.DesignPragmatic cluster randomised controlled trial.SettingArequipa, Peru.Participants4922 households.InterventionsHouseholds were randomised to one of four arms: advanced planning, leader recruitment, contingent group lotteries, or control.Main outcome measuresParticipation (allowing the house to be sprayed with insecticide) during the vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…The results from this trial are reported in detail elsewhere [41]. Briefly, Cycle 2 participation was high (over 80%) in the study area, with little difference across study arms (see Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The results from this trial are reported in detail elsewhere [41]. Briefly, Cycle 2 participation was high (over 80%) in the study area, with little difference across study arms (see Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Brigade chiefs could not plan that far ahead of time due to water shortages, health sector strikes, holidays, and a canine rabies outbreak.Households scheduled in advance were often not home for spray appointment.Advance scheduling was revised to 7–10 days ahead of spraying.Spray brigade schedule was intentionally “overbooked” to account for no-shows.Households are not able to plan for spraying when scheduled only 1 day prior.Planning prompts can help follow through on desired behavior. [3941]Offer planning prompts as well as email, text message, phone call or visit reminders to advance scheduled households.Few households chose email or text message remindersOnly call or visit reminders were offered.Those working during the day cannot participate.Provide more flexible scheduling options to households (evenings and weekends, more choice of spraying time).Evening hours were not feasible for the spray brigade, although frequently requested by households. Weekend spraying was used for “recuperation,” or to catch up, but could not be scheduled in advance.Households scheduling in advance could choose preferred appointment times during the regular spray day but not weekend or evening hours.Sprayer arrival time is unpredictable.Spray households according to pre-arranged schedule (rather than proceeding house-by-house down a block).If households scheduled in advance were not at home for spray appointment, sprayers could not “make up” the missed appointments by spraying nearby households, as these were also scheduled in advance.We staffed up extra sprayers to fill in when regular spray brigades could not accommodate the pre-arranged schedule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies did not specify a disease which the intervention was focused on specifically, apart from two studies targeting Chagas disease [43] and trachoma [66]. The studies targeted specific behaviors rather than diseases and merely described possible health effects of these behaviors, mostly a decrease of infectious pathogens causing a host of illnesses (e.g., diarrhea, pneumonia).…”
Section: Targeted Behaviormentioning
confidence: 99%
“…Finally, decision information was the least used category with 5 nudges using "translate information" through simplification and message reframing [38,52,58,60], 3 nudges using "provide social reference point" referring to role-models [39,43,48,49], and 2 nudges implementing "make information visible" through visualization of the future and providing visual feedback [44,52]. The results of each of the eight ethical criteria described in Table 3 are presented below one by one, and the findings are visualized in Figure 4 targeted behaviors during specified moments such as water disinfection, or involving a certain group (e.g.…”
Section: Choice Architecturementioning
confidence: 99%